The digital Field between the Rules of private law and ethical rules: European Union case study - PhD. Assistant Teacher Tareck Alsamara (The college of law and political science journal, 2024)
This article aims to study the issue of regulating the digital field through the rules of private law and ethical charters. Issues related to public law are outside the scope of this study. The study sheds light on the development of the issue at the level of the European Union, as it compares regulation according to legal rules and ethical regulation through Codes of ethics related to the topic. The descriptive approach is used to describe the evolving legal framework at the European Union level, as well as the ethical charters related to the digital field. The article also uses the historical approach to know the history and development of the issue at the European level, and the research concludes with a set of results centered around the European Union’s seriousness in providing an integrated and rapidly developing legal framework for the digital field. The European Union bodies interact around the digital field and their efforts harmonize with the problem of the unique international space in the field of digital law, through upgrading the rules of private law in member states.